Pengaruh Locus of Control terhadap Hubungan antara Ketidakpastian Lingkungan dengan Karakteristik Informasi Sistem Akuntansi Manajemen - Priyono Puji Prasetyo (The Indonesian Journal of Accounting Research, 2013)
This study is to identify the interactive effect of perceived environmental uncertainty and locus of control on management accounting systems design. Management accounting systems design is defined in term of perceived availability of characteristics of information.In this study it is hypothesized that as  perceived environmental uncertainty (PEU) increases, internal on the locus of control (LOC) scale will perceived information that has wider scope and more aggregated and is timely to be more usefull than do external on the locus of control scale. Data is selected using random sampling method. The units of analysis for responses of 45 managers - production, finance and marketing. Colection of data is performed using mail survey method. Multiple regression method is used to test the hypotheses.The results of this study indicate that there are empirical support to broadscope and timely information. However, there are not significant effect on aggregated information.